Mulberry moon [large type] - Anderson, Catherine (Adeline Catherine) (Anderson, Catherine (Adeline Catherine). Mystic Creek novel, 2017)
"After a career on the rodeo circuit, Ben Sterling longs to settle down on his farm in Mystic Creek, Oregon, and start a family like his brothers. The only woman to spark his interest is the new owner of the local café. Getting her attention won't be easy since she's determined to make it on her own"--